Penegakan Hukum Terhadap Pelaku Balap Motor Liar Pada Bulan Ramadhan - Fharansyah, Muhammad Syukran; Supusepa, Reimon; Sopacua, Margie Gladies (Faculty of Law Universitas Pattimura, 2025)
Illegal motorcycle racing is an unlawful act based on Articles 503, 510 and 511 of the Criminal Code as well as Articles 115 and 297 of Law Number 22 of 2009 concerning Road Traffic and Transportation. However, in its implementation, illegal motorcycle racing still occurs among the community, especially on Jalan A.Y. Patty, Ambon City during the month of Ramadan. The purpose of this research is to find out and discuss law enforcement efforts against illegal motorcycle racing perpetrators on Jalan A Y Patty and legal protection that can be provided to victims of other road users affected by illegal motorcycle racing in the month of Ramadan. The research method used in this writing is a normative legal research method with a legislative approach, a case approach and a conceptual approach, to answer the problems raised. The result of this study is that law enforcement efforts carried out by the Ambon Island Police and Lease Islands against illegal motorcycle racing in the month of Ramadan on Jalan A.Y. Patty, Ambon City are carried out in a preventive and repressive manner. Preventively, it is carried out by prevention in the form of socialization or lectures and appeals for the community, sweeping or raiding motor vehicles, and patrols targeted at the locations of motorcycle gang associations. Meanwhile, repressively, it is carried out in the form of imposing legal sanctions, namely ticket sanctions. And the form of legal protection for victims of traffic accidents affected by illegal motorcycle racing in the month of Ramadan is the provision of compensation by the perpetrator paying for vehicle damage experienced by victims of illegal motorcycle racing.